Biospheric Evolution Is Coarsely Deterministic - David Schwartzman (Journal of Big History, 2020)
Starting with the origin of life, I argue that the general pattern of the tightly coupled evolution of biota and climate on Earth has been the very probable outcome from a relatively small number of possible histories at the macroscale, given the same initial conditions. Thus, the evolution of the biosphere self-selects a pattern of biotic evolution that is coarsely deterministic, with critical constraints likely including surface temperature as well as oxygen and carbon dioxide levels in the atmosphere. Environmental physics and chemistry drive the major events in biotic evolution, including pho-tosynthesis and oxygenic photosynthesis, the emergence of new cell types (eucaryotes) from the merging of complemen-tary metabolisms and finally multicellularity and even encephalization.